Oxidative Cyclization Reactions Catalyzed by Designed Transition-Metal Complexes: A New Strategy for the Synthesis of Flavone, Quinolone, and Benzofuran Derivatives - Singh, Apurva; Singh, Sain; Ghosh, Kaushik; Ahmed, Naseem (Synthesis, 2023)
An efficient and convenient synthetic protocol is reported for the synthesis of 2-phenyl-4H-chromen-4-one, 2-phenylquinolin-4(1H)-one, and 11H-benzofuro[3,2-b]chromen-11-one derivatives from 2′-hydroxychalcones, 2′-aminochalcones, and 3-hydroxyflavones, respectively, using transition-metal catalysts and TEMPO as an oxidizing agent. This catalytic heterocyclization approach involves in situ free-radical generation as phenoxyl radicals were detected by EPR spectroscopic study and H2O2 was formed. The present method has numerous advantages, such as high atom-economy, less hazardous synthesis, benign solvent and auxiliaries, easy handling, and broader substrate scope with good to excellent product yields.
Keywords: transition-metal complexes; phenoxyl radical complex; catalytic reaction; oxidative cyclization; heterocyclization